The effect of drill exercise and reaction speed on the drive accuracy of beginner table tennis athletes - Suisdareni, Suisdareni; Tomoliyus, Tomoliyus (Jurnal Keolahragaan, 2021)
This study aimed to test (1) the differences of drill practice effect of a constant set of rising repetition and rising set of repetition continually on drive accuracy (forehand and backhand drive) for the beginner table tennis athletes, (2) the differences of the effect of high and low reaction speed on the drive accuracy (forehand and backhand drive) for the beginner table tennis athletes in Yogyakarta, and (3) the relation between drill practice and reaction speed on improving the drive accuracy (forehand and backhand drive) for the beginner table tennis athletes in Yogyakarta. This research used an experiment with a 2 x 2 factorial design. The sample was 20 beginner table tennis athletes in Yogyakarta, taken with random technique from a population of 38 athletes. The instrument for measuring reaction speed was the ruler drop test and for measuring the forehand and backhand drives was the precision of the drive accuracy. The data were analyzed using two-way ANOVA at significance level Î± = 0.05. The results of the study were as follows. (1) There were significant differences in the effect of a constant set of rising repetition and rising set of repetitions continually to drive accuracy (forehand and backhand drive) for the beginner table tennis athletes, as proven by the value of F = 7.538 and p = 0.014 <0, 05. The drill practice of a constant set of rising repetition was higher than the drill practice of a rising group of repetition always. (2) There was a significant difference effect of high and low reaction speeds to drive accuracy (forehand and backhand drive) for the beginner table tennis athletes, as proven by the value of F = 21.442 and p = 0.000 <0.05. High reaction speed was better than low reaction speed. (3) There was a significant relation between drill practice and reaction speed on improving punch drive accuracy (forehand and backhand drive) for beginner table tennis athletes, as proven by the value of F = 136.398 and p = 0.000 <0.05.